Evolution of Resistance in Cancer: A Cell Cycle Perspective - Dökümcü, Kağan; Farahani, Ramin M. (Frontiers in Oncology, 2019)
Resistance of neoplastic cells to therapy is considered a key challenge in the treatment of cancer. Emergence of resistance is commonly attributed to the gradual mutational evolution of neoplastic cells. However, accumulating evidence suggests that exogenous stressors could significantly accelerate the emergence of resistant clones during the course of a treatment. Herein, we review molecular mechanisms that regulate the evolution of resistance in a tumor with particular emphasis on the role of cell cycle.